(untitled) (Chemical Engineering Research Bulletin, 2021)
Split type room air conditioners (RACs) are very common nowadays. In Bangladesh, RAC manufacturers employ trial-error prototyping techniques in their design to increase the efficiency of RACs and the profitability of the plant. Computer modeling can be a great help to reduce the cost in the R&D stage to find the optimum design of RACs. In this study, modeling of heat transfer in the condenser of split type RACs employing the techniques of Computational Fluid Dynamics (CFD) was performed. To reduce the computational load the geometry was divided into small sections and geometric symmetries were also taken into account. For the simulation, the geometry and other relevant data were set in such a way so that they commensurate closely with real industrial data. An example data set for validation of simulation results were obtained from an AC manufacturer company, Elite Hitech Industries Ltd. The geometry was built using meshing techniques. Copper and aluminum were selected as materials for tubes and fins, respectively. R-22 was chosen as the refrigerant. Heat transfer and fluid flow were modeled using non-isothermal flow in a multi-physics environment. The main assumptions employed are laminar flow, extra coarse mesh size, constant air inlet temperature, perfect insulation between system and surroundings, and thin layer fins. The temperature distribution and heat transfer efficiency in the condenser, the impact of different refrigerant flow arrangements in the tubes have been studied in detail. This study leads to the finding of efficient refrigerant flow arrangements from the viewpoint of maximum heat transfer. Chemical Engineering Research Bulletin 21(2020) 20-25